Antidepressant-like activity of magnesium in the chronic mild stress model in rats: alterations in the NMDA receptor subunits - Pochwat, Bartłomiej; Szewczyk, Bernadeta; Sowa-Kucma, Magdalena; Siwek, Agata; Doboszewska, Urszula; Piekoszewski, Wojciech; Gruca, Piotr; Papp, Mariusz; Nowak, Gabriel (The international journal of neuropsychopharmacology, 2014)
Recent data suggests that the glutamatergic system is involved in the pathophysiology and treatment of major depressive disorder (MDD) and that the N-methyl-d-aspartate (NMDA) receptor is a potential target for antidepressant drugs. The magnesium ion blocks the ion channel of the NMDA receptor and prevents its excessive activation. Some preclinical and clinical evidence suggests also that magnesium may be useful in the treatment of depression. The present study investigated the effect of magnesium treatment (10, 15 and 20 mg/kg, given as magnesium hydroaspartate) in the chronic mild stress (CMS) model of depression in rats. Moreover, the effect of CMS and magnesium (with an effective dose) on the level of the proteins related to the glutamatergic system (GluN1, GluN2A, GluN2B and PSD-95) in the hippocampus, prefrontal cortex (PFC) and amygdala were examined. A significant reduction in the sucrose intake induced by CMS was increased by magnesium treatment at a dose of 15 mg/kg, beginning from the third week of administration. Magnesium did not affect this behavioural parameter in the control animals. CMS significantly increased the level of the GluN1 subunit in the amygdala (by 174%) and GluN2A in the hippocampus (by 191%), both of which were significantly attenuated by magnesium treatment. Moreover, magnesium treatment in CMS animals increased the level of GluN2B (by 116%) and PSD-95 (by 150%) in the PFC. The present results for the first time demonstrate the antidepressant-like activity of magnesium in the animal model of anhedonia (CMS), thus indicating the possible involvement of the NMDA/glutamatergic receptors in this activity.